Abjection of Body: Quest for Identity, Freedom and Maturity in Robert Cormier’s The Chocolate War (Bon Voyage, 2019)
This paper analyzes abjection of body in Robert Cormier’s The Chocolate War. The young adult protagonist of The Chocolate War, Jerry Renault encounters social and psychological abjections. In addition this paper discusses how social and psychological abjections work in The Chocolate War. By and large this paper argues that abjection of body supports to quest identity and freedom. It also discusses how the young adult protagonist employs his body to obtain identity and freedom. Therefore, this paper contends that abjection is necessary condition each individual passes through before reaching into maturity, the condition in which they realize the need for conforming to the society. For the analytical purpose, it draws the insights of abjection from Julia Kristeva and Karen Coats. This paper provides an opportunity to know the young adult body and the conditions of abjection. Moreover this paper facilitates to know the ways of triumphing over abjection and results the young adult obtains after overpowering abjection.